Pengaruh Mutasi D802N pada Aktivitas Polimerase DNA Pol I ITB-1 - L. Ambarsari; F. Madayanti; M. R. Moeis; Akhmaloka Akhmaloka (Institute for Research and Community Services (LPPM) ITB, 2006)
D802N mutant gene of DNA Pol I ITB-1 was constructed and expressed in Escherichia coli. The crude enzyme was characterized and compared to that the wild-type. The optimum pH and temperature of the mutant was slightly differences with those the wild-type. The optimum pH and temperature of the mutant were 9.0 and 50oC, while the wild-type were 7.4 and 65oC, respectively. The differences of the above properties were followed by decreasing of specific activities of the mutant (1.34 unit/mg protein) 2.7 times lower to that the wild-type (3.71 unit/mg protein). Meanwhile the catalytic efficiency (kcat/Km ) of the mutant decreased 2 times lower compared to that the wild-type. Mutation at D802N of DNA pol I ITB-1 caused decreasing on the mutant affinity to the substrate and thus loss activity and instability of the enzyme.